PHYTOPATHOLOGICAL AND MOLECULAR CHARACTERISTICS OF PHYTOPHTHORA INFESTANS ISOLATES COLLECTED ON RESISTANT AND SUSCEPTIBLE POTATO GENOTYPES - Kuznetsova, Maria; KOZLOVSKY, B.E.; BEKETOVA M.P; SOKOLOVA E.A; MALYUCHENKO O.P; ALEKSEEV Ya., I.; ROGOZINA, E.V.; KHAVKIN, E.E. (Zenodo, 2016)
Recently new aggressive lineages have emerged in the West European populations of Phytophthora infestans and have overcome many elite potato varieties known for high late blight resistance. These lineages have rapidly moved eastward displacing the previously known strains of the pathogen. To evaluate the changes in Ph. infestans populations which spread across the North-Western Russia, we hawe realized in 2013-2014 two pilot experiments with isolates obtained from leaves collected in the field potato plots of the Pushkin laboratories of the N.I. Vavilov Institute of Plant Genetic Resources (VIR) in the Leningrad Region of Russia. In this study the phytopathologic characteristics of Pushkin isolates of Ph. infestans were supplemented, for the first time, with the molecular evidence. Potato leaves naturally infected with Ph. infestans were collected from variety Sarpo Mira, which manifested high level of late blight resistance in the European countries, and several interspecific hybrid clones from the VIR collection. The ability of the pathogen to damage various potato genotypes was evaluated in field and laboratory trials. R -gene virulence phenotypes, mating type, aggressiveness and response to fungicide metalaxyl were assessed. Mating type identification was based on the oospore development and the presence of CAPS marker. The microsatellite analysis of Ph. infestans isolates was conducted using the established set of primers for 12 SSR loci. We have confirmed the previously observed tendency for complexity of the race profile in the Pushkin population of Ph. infestans and enhanced proportion of A2 genotypes, which is consistent with the general trend observed in the Western and Central Europe up to 2013. The isolates with A2 mating type were sensitive to metalaxyl. Indices of aggressiveness of strains collected from the leaves of potato genotypes highly resistant to late blight were significantly lower than in the case of more susceptible varieties. The indices for aggressiveness did not expressly match the profiles of virulence genes in the isolates. We presume that in 2013, isolates of Ph. infestans were collected late in the season when only resistant and moderately resistant potato plants stayed alive. In 2014, at the earlier stage of late blight progression, we also collected more aggressive isolates from susceptible potato genotypes. In the 2013 and 2014 sets of Pushkin isolates, we have not discerned the aggressive genotypes from the Western Europe.